Potensial Daerah Aliran Sungai di Jawa Barat yang Berpengaruh Terhadap Lumbung Pangan Nasional dengan Indikator Qmaximum/Qminimum - Budi Wicaksono; John Paulus Pantouw; Mekar Ageng Kinasti (Journal of Sustainable Civil Engineering (JOSCE), 2024)
The development of the times, especially the development of global climate change and the rapid increase in population in River Watershed areas, will influence the condition of the watershed. The increasing and excessive use of natural resources to meet human needs in watershed areas will result in several things, including increased land change, decreased soil capacity and disruption of water balance. High population growth rates will increase competition between providing land for food production and other needs. In line with population growth, the population's need for food is also increasing, because the size of the population is directly related to food supply. This research aims to analyze the potential size of 5 sub-watersheds in West Java which influence the national food storage, so that it is hoped that it can provide suggestions for ways out according to the characteristics of each sub-watershed in terms of strengthening national food security. From the results of research conducted on 5 sub-watersheds in West Java with indicators of the ratio between maximum discharge and minimum discharge (Qmax/Qmin), the results showed that the average value of the ratio between maximum discharge and minimum discharge (Qmax/Qmin) for the Citarik River -The buffer is 11.77 which is included in the "fair" category, for the Cimandiri-Leuwilisung River it is 66.59 which is included in the "very bad" category, for the Citanduy-Pataruman River it is 156.16 which is included in the "very bad" category for Cikeruh-Cikuda was 224.60 which was included in the "very bad" category, and for the Cisangkuy-Kamasan River it was 99.17 which was included in the "very bad" category. Based on the values ​​above, in general, sub-watersheds in West Java are included in the "very poor" category, where the condition of the existing sub-watersheds needs to be improved further so that they can be increased to the "adequate" category, so that they can also increase the reliability of food security in Java. West in particular and increasing the reliability of national food security in general. The suggestions related to the results of the research that have been carried out are that it is necessary to improve the condition of several sub-watersheds in West Java by means of watershed conservation or watershed improvement approaches in other ways so that the condition of the watershed can improve better, so as to increase the reliability of food security in West Java in particular. and increasing the reliability of national food security in general. Key words: maximum discharge, minimum discharge, food security, watershed potential